Undergrade nursing students experiences with hand hygienic principles in clinical studies: A qualitative study - Aune, Anne Grethe; Sundal, Jorun Satre; Storvig, Eline; Aasland, Jenny; Andrè, Beate (Nordisk Tidsskrift for Helseforskning, 2022)
A significant part of the nurse’s education takes place in the clinical studies, supervised by nurse`s. This study has been conducted to hear the student’s experiences, how they learn the adherence to hand hygienic principles in clinical studies. We used a descriptive and exploratory design with focus group interviews. The data were analysed using qualitative content analysis. The analysis resulted in two main topics, factors that promoted and inhibited student learning. Clear guidelines, procedures and feedback from supervisors, promoted learning. Lack of hand hygiene facilities, time pressures, complex learning situations in adequate recognition and the supervisors’ non-compliance were inhibitory factors. Supportive and encouraging feedback from the tutors were positive factors for student learning. The study shows that nurses in clinical practice were a role model for students and important to learn the correct hand hygienic principles in clinical practice.